Spacelike surface families interpolating common asymptotic curves in Minkowski 3-space - Almoneef, Areej A.; Abdel-Baky, Rashad A. (Frontiers in Physics, 2025)
In this paper, we propose a method for constructing families of spacelike surfaces in Minkowski 3-spaceE13 that share Bertrand curves as asymptotic curves. By using marching-scale functions, we derive the necessary conditions, provide flexible formulations, and establish a framework for constructing mutual spacelike Bertrand curves. Examples show how different functions generate surfaces interpolating the common asymptotic curves, offering new insights for geometric modeling and ruled surface theory.